Frog leap algorithm for homology modelling in grid environment. (2016) - Ramyachitra, D.; Kumar, P. Pradeep
This research work shows how homology modelling works for protein sequences in grid environment based on the relevance match from the database. In First Come First Served (FCFS) strategy, the protein sequence is scheduled to the resource on FCFS order and processed until completion. On average it takes more time to search sequences and users may wait a long time for results. To overcome this, FCFS is implemented in grid. Here the time taken to process the sequences gets reduced, but the inputs are processed one by one. To overcome the maximum time execution and users' waiting time, Frog Leap Algorithm has been used for grid scheduling. The scheduling is done based on the size of the protein sequence. The system that takes the minimum time to process the particular protein sequence is found out initially in grid, through which the time complexity for scheduling has been improved.